Determination of Locations for Planting Poles to Support Fiber Optic Cable Networks with the Moora Method - Bahri, Anggi Adhilah; Rahmadani, Rahmadani; Khair, Husnul (International Journal of Informatics, Economics, Management and Science; Vol 3 No 1 (2024): IJIEMS (January 2024)DO - 10.52362/ijiems.v3i1.1217, 2024)
Telecommunication network is a series of telecommunications equipment and accessories used in conducting telecommunications activities. To build an optical network, the most important thing is to plant poles which will be used as network connectors . Pole planting is done based on several factors. In considering some of these factors, of course the company must make the right decision so that the projects carried out are in accordance with the company's targets. Making decisions manually will result in inaccurate and precise results. To reduce inaccuracies in making a decision, we need a system that can help and support companies in making a decision. The MOORA method works by giving weight to each specific criterion. From the weighting evaluation, the results with the highest ranking will be taken to determine decision making. From the results of the trials carried out, the best alternative system and analysis results were obtained from 20 data, namely jl.tuamang with community demand criteria of 47 people, population density of 372 people, moderate location access and distance between pillars of 45 meters with a result of 0.1499.